Undergradute Students' Perspectives on Digital Literacy in Minimizing the Spread of Hoax - Qonitah, Ainul; Sulistyaningrum, Siti Drivoka (ENGLISH FRANCA : Academic Journal of English Language and Education, 2024)
Hoaxes have been rampant on various social media platforms. A lack of digital literacy skills causes the ongoing hoaxes to spread. This study aims to analyse undergraduate students' perspectives on good digital literacy skills that can minimize the spread of hoaxes. The current study uses a survey research method to gain insights into the perspective of undergraduate students. Respondents in this study were 21 undergraduate students of the Islamic State University of Sultan Maulana Hasanuddin Banten in the English Education Department. The result of this study indicates that most students can handle the hoax news, even though some are still spreading it. Besides that, the type of hoax often accepted by students is social politics, which spreads through Facebook applications.